Analysis of social science e-modules on the practicality of Learning PGSD students - Prihatin Sulistyowati; Yulianti Yulianti (Universitas Kanjuruhan Malang, 2023)
The researcher aims to develop the E-Module and see the practicality of using the E-Module. The method used in this research is research and development. The development model in this development research uses a 4-D model by following the steps: Define, Design, Development and Disseminate. Apart from that, there are also observations and interviews to see how far the practicality of learning using this E-Module is. E-Modules can increase students' interest in receiving elementary social studies learning. The developed E-Module has been tested by several experts and is valid in use and use so that it can be seen that this E-Module is very well used for learning. This e-module is also a practical medium in learning and can be used in any situation regardless of distance and time and can assist in the online social studies learning process for PGSD students.